Studies on Anticancer Effect of Methanolic Leaf Extract of Justicia gendarussa on Lung Cancer Cell Line - Lavanya Ravi; Vimal S (Wolters Kluwer Medknow Publications, 2024)
ObjectiveThe aim of study's goal was to look into the anticancer efficacy of a methanolic extract of Justicia gendarussa against a lung cancer cell line. Materials and MethodsCell viability assays and cell and nuclear morphology examinations were used to evaluate the anticancer efficacy against methanolic extract of Justicia gendarussa on lung cancer cell lines. The IC50 doses were calculated using different concentrations of Justicia gendarussa extract (0, 10, 20, 40, 60, and 80 μg/mL). ResultsThe results of MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl-tetrazolium bromide) assay revealed that the percentage of viability in treated cells was significantly lower as compared with untreated control groups, which represented as 100%, and an inhibitory concentration of 40 μg/mL was observed. Under a phase-contrast microscope, morphological changes revealed cell shrinkage and cytoplasmic membrane blebbing. The apoptotic nuclei (intensely colored, broken nuclei, and compacted chromatin) were examined under a fluorescence microscope. ConclusionsThe outcome of the research work on Justicia gendarussa was investigated for anticancer properties. The results revealed the proapoptotic and cytotoxic effects of Justicia gendarussa extract on lung cancer cell lines. From the above results and findings, it could be concluded that the Justicia gendarussa methanolic leaf extract exhibited potent anticancer activity against a lung cancer cell line. Further study needs to be conducted to investigate the active chemicals in the extract as well as the molecular mechanisms underlying its anticancer benefits.